Spatial and temporal variability in MLT turbulence inferred from in situ and ground-based observations during the WADIS-1 sounding rocket campaign - Strelnikov, Boris; Szewczyk, Artur; Strelnikova, Irina; Latteck, Ralph; Baumgarten, Gerd; Lübken, Franz-Josef; Rapp, Markus; Fasoulas, Stefanos; Löhle, Stefan; Eberhart, Martin; Hoppe, Ulf-Peter; Dunker, Tim; et al. (Annales Geophysicae, 2017)
In summer 2013 the WADIS-1 sounding rocket campaign was conducted at the Andøya Space Center (ACS) in northern Norway (69 N, 16 E). Among other things, it addressed the question of the variability in mesosphere/lower thermosphere (MLT) turbulence, both in time and space. A unique feature of the WADIS project was multi-point turbulence sounding applying different measurement techniques including rocket-borne ionization gauges, VHF MAARSY radar, and VHF EISCAT radar near Tromsø. This allowed for horizontal variability to be observed in the turbulence field in the MLT at scales from a few to 100 km. We found that the turbulence dissipation rate, ε varied in space in a wavelike manner both horizontally and in the vertical direction. This wavelike modulation reveals the same vertical wavelengths as those seen in gravity waves. We also found that the vertical mean value of radar observations of ε agrees reasonably with rocket-borne measurements. In this way defined <ε radar > value reveals clear tidal modulation and results in variation by up to 2 orders of magnitude with periods of 24 h. The <ε radar > value also shows 12 h and shorter (1 to a few hours) modulations resulting in one decade of variation in <ε radar > magnitude. The 24 h modulation appeared to be in phase with tidal change of horizontal wind observed by SAURAMF radar. Such wavelike and, in particular, tidal modulation of the turbulence dissipation field in the MLT region inferred from our analysis is a new finding of this work.